A two-step homogeneous assay for apolipoprotein E-containing high-density lipoprotein-cholesterol - Takahashi, Yuji; Ito, Yasuki; Sakurai, Toshihiro; Wada, Norio; Nagasaka, Atsushi; Fujikawa, Masato; Chiba, Hitoshi; Hui, Shu-Ping (Annals of clinical biochemistry, 2019)
Apolipoprotein E-containing high-density lipoprotein shows antiatherogenic properties in vitro. There is a need for a homogeneous assay to determine the concentration of apolipoprotein E-containing high-density lipoprotein for in vivo studies. In the proposed homogeneous assay, lipoproteins other than apolipoprotein E-containing high-density lipoprotein were eliminated in the first step. Apolipoprotein E-containing high-density lipoprotein-cholesterol was measured in the second step. The control study used a 13% polyethylene glycol precipitation assay (control assay). The homogeneous assay showed good performance in validation studies. In subjects with normal liver function ( n = 78), a significant correlation was found between the control assay and the homogeneous assay ( r = 0.824). Serum apolipoprotein E-containing high-density lipoprotein cholesterol concentrations, determined by the control assay and the homogeneous assay, respectively, were 0.05 (0.04-0.10) (median [25th-75th percentile]) mmol/L and 0.10 (0.06-0.13) mmol/L for healthy individuals ( n = 12), and 0.03 (0.01-0.13) mmol/L and 0.02 (0.01-0.02) mmol/L for patients with cholestasis ( n = 6). The results indicate that the homogeneous assay recovers cholesterol contained in physiological apolipoprotein E-containing high-density lipoprotein, but not in pathological apolipoprotein E-containing high-density lipoprotein from cholestatic patients. The proposed two-step homogeneous assay enables selective measurement of physiological apolipoprotein E-containing high-density lipoprotein cholesterol in common autoanalysers. This assay might uncover a role for apolipoprotein E-containing high-density lipoprotein in physiological conditions.